Can earlier BCG-Japan and OPV vaccination reduce early infant mortality? A cluster-randomised trial in Guinea-Bissau - Peter Aaby; Sanne Marie Thysen; Ane Bærent Fisker; Amabelia Rodrigues; Christine Stabell Benn; Aksel Jensen; Igualdino da Silva Borges; Jailson Martins; Alexander Dahl Stjernholm; Jesper Sloth Hansen; Leontino Manuel Vieira da Silva; Justiniano Sebastião Durga Martins (BMJ Global Health, 2024)
Objective To assess the effect of providing BCG and oral polio vaccine (OPV) at an early home visit after delivery.Design Cluster-randomised trial, randomising 92 geographically defined clusters 1:1 to intervention/control arms.Setting Bandim Health Project Health and Demographic Surveillance System, Guinea-Bissau.Participants 2226 newborns enrolled between July 2016 and August 2019.Interventions In both arms, newborns received a home visit within 72 hours after birth. In intervention clusters (n=46), BCG and OPV were provided at the home visit.Main outcome measure Rates of non-accidental mortality were compared in Cox proportional hazards models from (last of) day 1 or enrolment, until (first of) day 60 or registration of non-trial vaccines.Results A total of 35 deaths (intervention: 7, control: 28) were registered during the trial. Providing BCG and OPV reduced non-accidental early infant mortality by 59% (8–82%). The intervention also reduced non-accidental hospital admissions. The intervention had little impact on growth and BCG scarring and tended to increase the risk of consultations.Conclusions The trial was stopped early due to lower-than-expected enrolment and event rates when 33% of the planned number of newborns had been enrolled. Despite the small size of the trial, the results support that early BCG and OPV vaccinations are beneficial and reduce early child mortality and morbidity.Trial registration number ClinicalTrials.gov Registry (NCT02504203).